(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background Burnout is a significant psychological issue affecting individuals, communities, and organizations. It is characterized by emotional exhaustion, depersonalization, and reduced professional efficacy. Despite efforts for global recognition, it remains a complex issue with no consensus on analytic criteria or standard criteria, hindering targeted interventions and support systems. Objective The study investigates the prevalence and associations of burnout among healthcare specialists and paramedical staff in Punjab, Pakistan, identifying factors causing burnout, working hours, job dissatisfaction, and mental health outcomes. Methods This cross-sectional study used online surveys to collect data on burnout among healthcare practitioners. A validated questionnaire, Estudillo and Mendieta, was used for the study, which was divided into four parts. Data was collected from November 2024 to February 2025 and analyzed using IBM SPSS software 21 version. Results The study surveyed 341 participants, primarily males, and found that Depersonalization was the most prevalent scale among the three MBI subscales. The profession was divided into various departments, including house officers, GPs, MOs, PGs, nursing, and pharmacy. HCPs reported higher levels of burnout due to improper shift work. Conclusion The research found a 25.5% incidence rate of burnout among female practitioners and younger healthcare professionals, with experienced practitioners reporting lower levels, possibly due to better-coping mechanisms in demanding practice. Recommendations Implement mental health prevention initiatives for healthcare practitioners to reduce burnout and improve stress management. Dynamic measures should be adopted to foster self-regulatory behaviors and reduce job-related negative consequences